The understanding of contract documentation in project implementation - Madon, Zulkifly (2005)
The contract obligation by any party in any contract will be interpreted by terms and contents of the documents laid down in the contract. Effective interpretation and understanding of the contractual obligations will be much dependent on the clarity of the documents in translating the needs and requirements implied as in the agreement. Without proper understanding of the documents may lead to the different interpretations which may result in unnecessary contractual problems such as disputes, unnecessary claims, reworks, shoddy works, and even litigation. The aim of this study is to identify the importance and the level of understanding of contract documentation in our local construction industry. The study conducted with reference to the indigenous group of contractors who participate in contract implementation in Public Sector Projects experiences. The methodology adopted for the study includes interviews with panel of experts that have vast experience in contract administration and industry wide questionnaire survey among the Bumiputra contractors that involved in JKR projects. The data collected were analysed using content analysis method and using appropriate statistical method such as frequency analysis and relative index method. The study has determined from the viewpoints of expert panel that the expected level of understanding toward contract documentation must be very high. However the levels of current understanding among the contractors are fairly moderate. Therefore there is an urgent need to improve this situation. Apart from that the study also established factors that inhibit the understanding of contract document as well as the factors that can help to improve the understanding of contract documents for the contractors